Oh, are you awake? - Shea, Bob (Candlewick Press, 2024)
"There once was a very sleepy penguin, who was best friends with a not-so-sleepy lion... A pitch-perfect comedy for anyone who has ever craved sleep -- and anyone too full of energy to settle down." --